Autism Spectrum Disorder (ASD): Understanding Beyond Labels - Agarwal M (Disease and Health: Research Developments Vol. 9, 2025)
Autism Spectrum Disorder (ASD) is increasingly acknowledged as a varied neurodevelopmental condition, with its global prevalence, including in India, demonstrating a notable upward trend. It is imperative to transcend reductive labels and misconceptions that frame ASD as a disease. Instead, ASD should be understood as a spectrum of neurological differences that influence individuals’ perception, information processing, communication, and interaction with their environment. Recent advances in scientific research, both globally and within India, have significantly enhanced the understanding of ASD. Emerging evidence highlights a multifactorial etiology involving genetic, environmental, and neurobiological components. This article provides a comprehensive overview of the core characteristics of ASD, addresses prevalent myths, examines etiological and diagnostic frameworks, and reviews contemporary, evidence-based strategies aimed at promoting autonomy, psychosocial well-being, and inclusive participation for children on the spectrum.